2002
DOI: 10.1074/jbc.m203067200
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase-1 Protects from CD95-induced Apoptosis

Abstract: Through the induction of apoptosis, CD95 plays a crucial role in the immune response and the elimination of cancer cells. Ligation of CD95 receptor activates a complex signaling network that appears to implicate the generation of reactive oxygen species (ROS). This study investigated the place of ROS production in CD95-mediated apoptosis and the role of the antioxidant enzyme glutathione peroxidase-1 (GPx1). Anti-CD95 antibodies triggered an early generation of ROS in human breast cancer T47D cells that was bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 57 publications
1
46
1
1
Order By: Relevance
“…Our findings are consistent with the known inhibitory effect of antioxidant selenoproteins on apoptosis (Fu et al, 2001;Gouaze et al, 2002). Previous studies reported elevated expression of detoxification and repair enzymes in Se-deficient mouse livers (Reiter and Wendel, 1984;Carlson et al, 2004), as well as in cells treated with high levels of Se (El-Bayoumy and Sinha, 2004;Zhao et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…Our findings are consistent with the known inhibitory effect of antioxidant selenoproteins on apoptosis (Fu et al, 2001;Gouaze et al, 2002). Previous studies reported elevated expression of detoxification and repair enzymes in Se-deficient mouse livers (Reiter and Wendel, 1984;Carlson et al, 2004), as well as in cells treated with high levels of Se (El-Bayoumy and Sinha, 2004;Zhao et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…This is surprising, as the efficacy of pharmacological antioxidants such as GSH, NAC, deferoxamine (283,420,425), and antioxidant enzymes such as catalase or GPx (149,283) in preventing apoptosis have been shown by several groups. Other studies, however, were unable to demonstrate any role of antioxidants in preventing apoptosis (15,66,122).…”
Section: A Extrinsic Pathways Of Cell Death and Regulation By Rosmentioning
confidence: 98%
“…It was reported that a caspase-1 inhibitor, Ac-YVAD-cmk, blocked a later burst of ROS during GSH depletion when added early in the death program (37); thus caspase-1 may also play a role in the later phase of ROS generation, and protection from apoptosis by Bcl-X L may be related to its ability to serve as "anti-oxidant" in this system (38). Consequently, the decline of the expression of Bcl-X L might also contribute to the delayed increase of ROS.…”
Section: Discussionmentioning
confidence: 99%